From: archive De Bosch Kemper, map 67, no. 109; with a dedication by L'Hermier des Plants, dated June 4, 1880, on back
From: archive De Bosch Kemper, map 67, no. 109; with a dedication by L'Hermier des Plants, dated June 4, 1880, on back.